2007
DOI: 10.1016/j.bbrc.2007.07.154
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of AMP-activated protein kinase and p38 mitogen-activated protein kinase signaling in skeletal muscle

Abstract: AMP-activated protein kinase (AMPK) is widely recognized as an important regulator of glucose transport in skeletal muscle. The p38 mitogen-activated protein kinase (MAPK) has been proposed to be a component of AMPK-mediated signaling. Here we used several different models of altered AMPK activity to determine whether p38 MAPK is a downstream intermediate of AMPK-mediated signaling in skeletal muscle. First, L6 myoblasts and myotubes were treated with AICAR, an AMPK stimulator. AMPK phosphorylation was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…1B, adiponectin-stimulated p38 MAPK activation was not affected in the AMPK␣2-suppressed cells. This observation is consistent with a report that AMPK and p38 MAPK pathways are dissociated in skeletal muscle (9).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…1B, adiponectin-stimulated p38 MAPK activation was not affected in the AMPK␣2-suppressed cells. This observation is consistent with a report that AMPK and p38 MAPK pathways are dissociated in skeletal muscle (9).…”
Section: Resultssupporting
confidence: 94%
“…It has been reported that AMPK functions as an upstream kinase of p38 MAPK in regulating glucose uptake stimulated by stretch and AICAR, however, it is still controversial whether AMPK-stimulated p38 MAPK activation is a common mechanism in skeletal muscle (4,9,12,26). Suppression of AMPK␣2 expression significantly affected AMPK activity and impaired the ischemia-induced p38 MAPK activation in ischemic heart (12), suggesting a role of AMPK␣2 in the activation of p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Because a single AICAR injection does not induce HIF-1␣ in normoxic conditions (29,38) and a single AICAR injection induced AMPK phosphorylation and not p38 MAPK in the present study (in accordance with previous findings) (1,20,54), the AICAR injection protocol applies a model more specific than an exercise protocol to investigate the potential role of AMPK/PGC-1␣ signaling in regulation of VEGF expression. Because a single AICAR injection does not induce HIF-1␣ in normoxic conditions (29,38) and a single AICAR injection induced AMPK phosphorylation and not p38 MAPK in the present study (in accordance with previous findings) (1,20,54), the AICAR injection protocol applies a model more specific than an exercise protocol to investigate the potential role of AMPK/PGC-1␣ signaling in regulation of VEGF expression.…”
Section: Pgc-1␣ Is Required For Ampk-mediated Increases In Vegf Expresupporting
confidence: 91%
“…It has been suggested by some (26), but not all (20), that AMPK may lie upstream of p38 MAPK. It has been suggested by some (26), but not all (20), that AMPK may lie upstream of p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%